A method for preparing HNT-modified polymer composite membrane
Through the preparation method of HNT modified polymer composite membrane, the problem of poor comprehensive performance and high cost of flow battery separators is solved, and efficient and stable flow battery performance is achieved, which is suitable for a variety of systems.
Patent Information
- Application Number
- CN202411719104.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-11-28
AI Technical Summary
The comprehensive performance of existing flow battery separators is poor, expensive, and cannot be applied to multiple systems, which limits the large-scale application of flow batteries.
The preparation method of HNT modified polymer composite film was adopted, and dealuminized HNT was prepared by mixed acid etching method, and combined with sulfonated polyether ether ketone. The SPEEK/HNT composite film was prepared by solution casting method to improve its ion selectivity and mechanical properties.
It achieves high ionic conductivity, excellent ion selectivity, good chemical stability and mechanical properties, reduces the preparation cost, is suitable for a variety of liquid flow battery systems, and extends the cycle life of the battery.
Smart Images

Figure CN119230863B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of liquid flow battery diaphragms, and in particular relates to a method for preparing an HNT-modified polymer composite membrane. Background Art
[0002] A series of renewable energy sources such as wind and solar energy that are currently in common use have inherent problems of intermittency and instability, and a highly safe, environmentally friendly, large-scale energy storage technology is urgently needed. Liquid flow batteries have very broad application prospects in the field of large-scale energy storage due to their high safety, environmental friendliness, long cycle life, and separation of energy and power. As a key component of liquid flow batteries, the diaphragm separates the positive and negative electrolytes to prevent cross-contamination, and is responsible for transporting carriers and maintaining charge balance. An ideal composite diaphragm should have the following characteristics: high ionic conductivity, high ion selectivity, high chemical stability, and low cost.
[0003] Currently, perfluorosulfonic acid membrane (Nafion) is widely used in commercial applications due to its high proton conductivity and chemical stability. However, its severe ion permeation and high price have hindered its further application. Sulfonated polyetheretherketone (SPEEK), as a fluorine-free hydrocarbon-based diaphragm material, is a polyetheretherketone modified by sulfonation reaction, which has high chemical stability, thermal stability and excellent mechanical properties. SPEEK has low cost and stable structure. Its ion conductivity and ion selectivity can be regulated by changing the degree of sulfonation. Its preparation conditions are mild and suitable for large-scale production. However, with the increase of the degree of sulfonation, although high-sulfonation SPEEK has more cation exchange groups and higher ion conductivity, its mechanical properties will decrease, and it will lead to the enhanced permeability of SPEEK membrane to active substances in the electrolyte, affecting the stability and efficiency of the flow battery.
[0004] Perfluorosulfonic acid membranes, such as Nafion membranes, are currently common commercial membranes for flow batteries, but they are expensive and have poor ion selectivity, leading to capacity decay and water migration in flow batteries. Therefore, the preparation of composite membranes with low cost, long service life, excellent comprehensive performance and applicable to a variety of systems is an urgent problem to be solved in order to promote the large-scale application of flow batteries. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing an HNT-modified polymer composite membrane to solve the problems of poor comprehensive performance, high cost and inapplicability to a variety of systems of existing flow battery separators.
[0006] The technical solution adopted by the present invention is:
[0007] A method for preparing a HNT-modified polymer composite membrane comprises the following steps:
[0008] S1: Preparation of dealuminated HNTs;
[0009] S2: Preparation of modified HNTs using dealuminated HNTs;
[0010] S3: Preparation of sulfonated polyetheretherketone;
[0011] S4: ionization treatment of sulfonated polyetheretherketone;
[0012] S5: Prepare HNT-modified polymer composite membrane using the modified HNT and sulfonated polyetheretherketone or perfluorosulfonic acid membrane obtained in S4.
[0013] Further, the S1 includes:
[0014] S11: placing HNT into a mixed acid solution and controlling the mass volume ratio of HNT to acid;
[0015] S12: stirring the mixed solution to perform dealumination operation on the HNT;
[0016] S13: The product obtained in S12 is washed with deionized water until it becomes neutral, and dried to obtain dealuminated HNT.
[0017] Furthermore, in said S11,
[0018] The mixed acid is a mixed solution consisting of HCl solution and H2SO4 solution; the concentration of H2SO4 solution is 1.0~3.0 M;
[0019] The mass volume ratio of HNT to HCl solution is 1 / 30~1 / 10 g / mL; the mass volume ratio of HNT to H2SO4 solution is 1 / 20~1 / 5 g / mL;
[0020] In S12, the mixed solution is stirred at 20°C to 60°C for 3 to 6 hours.
[0021] Further, the S2 includes:
[0022] S21: placing the dealuminated HNT obtained in S1 into an alkaline solution;
[0023] S22: reacting at a constant temperature;
[0024] S23: The product is cleaned with deionized water and dried to obtain modified HNTs.
[0025] Furthermore, in S21,
[0026] The alkaline solution is any one of sodium hydroxide, potassium hydroxide, sodium chloride and potassium chloride; the concentration of the alkaline solution is 0.5~2.0 M;
[0027] In S22, the temperature is 40-80 °C and the reaction time is 48-72 h;
[0028] The structure of the modified HNT obtained in S23 is a cube.
[0029] Further, the S3 includes:
[0030] S31: Add concentrated sulfuric acid to n containers respectively; add polyetheretherketone to each container, n≥2, and the container capacity is 25~50 mL;
[0031] S32: stirring the mixed solution in each container;
[0032] S33: mixing the solutions in the n containers together and stirring;
[0033] S34: The reactant is washed with deionized water and dried to obtain sulfonated polyetheretherketone.
[0034] Further, in S31, the mass volume ratio of polyetheretherketone and concentrated sulfuric acid in each container is 1 / 15-1 / 10 g / mL;
[0035] In S32, stirring at 20°C to 60°C for 40 to 60 min;
[0036] In S33, stirring is performed at 60-80°C for 20-40 min at a stirring speed of 500-700 rpm.
[0037] Further, the S4 includes:
[0038] S41: placing the sulfonated polyetheretherketone obtained in S3 in an alkaline solution and soaking it at a constant temperature;
[0039] S42: washing the product obtained in S41 with deionized water until it becomes neutral, and drying it to obtain ionized sulfonated polyetheretherketone;
[0040] In the S41,
[0041] The alkaline solution is any one of sodium hydroxide, potassium hydroxide, sodium chloride and potassium chloride; the concentration of the alkaline solution is 0.5~2.0 M;
[0042] The temperature is 40~60℃; the soaking time is 2~4 hours.
[0043] Further, the S5 includes:
[0044] S51: adding the ionized sulfonated polyetheretherketone or the cut and dried perfluorosulfonic acid membrane obtained in S4 into the solvent and stirring;
[0045] S52: adding the modified HNT obtained in S2 and stirring;
[0046] S53: performing ultrasonic treatment, followed by drying, to obtain an HNT-modified polymer composite membrane;
[0047] If the shredded and dried perfluorosulfonic acid membrane is used in S51, the obtained HNT-modified polymer composite membrane needs to be heated in an ionizing solvent with a concentration of 0.5~2.0 M for 1.0 h~2.0 h, and then immersed in deionized water for storage; the ionizing solvent is any one of NaOH, KOH, and H2SO4; the heating temperature is 50~70℃.
[0048] Furthermore, in S51,
[0049] The solvent is any one of dimethyl sulfoxide, dimethylformamide, and dimethylacetamide; the mass volume ratio of sulfonated polyetheretherketone to organic solvent is 1 / 20-1 / 32 g / mL; stirring is performed at a temperature of 58-62°C for 2-6 hours;
[0050] In S52, the mass of modified HNT is 1-3% of the mass of sulfonated polyetheretherketone or perfluorosulfonic acid membrane;
[0051] In S53, the ultrasonic treatment time is 14-16 min; the solution casting method is used for drying; the drying process is drying at 78-82°C for 11.5-12.5 h, and then heating to 98-102°C for drying for 1.8-2.2 h.
[0052] The beneficial effects of the present invention are:
[0053] HNT is halloysite nanotube, a naturally formed aluminum silicate mineral with a unique tubular structure. The present invention first obtains a structurally stable modified HNT material by using a mixed acid (HCl+H2SO4) etching method combined with alkali treatment, and then uses a refined homogenization method to prepare SPEEK, and then the two are blended in an organic solvent to obtain a SPEEK / HNT composite membrane by a dissolution casting method. Due to the universality of the use of modified halloysite, the modified HNT is also used to modify PFSA, and the two are blended in an organic solvent and a PFSA / HNT composite membrane is obtained by a solution casting method. Compared with the prior art, the present invention has the following significant advantages and beneficial effects:
[0054] 1. The present invention prepares sulfonated polyetheretherketone short chains by refinement, so that each short chain can be uniformly grafted with sulfonic acid groups, and then the prepared refined and homogeneous SPEEK is blended to generate sulfonated polyetheretherketone long chains. Compared with the traditional one-time preparation of sulfonated polyetheretherketone long chains, this method can shorten the grafting distance of sulfonic acid groups on each chain segment, and make the grafting number and grafting distance of sulfonic acid groups more uniform, and the sulfonation degree of the obtained SPEEK is more uniform.
[0055] 2. The present invention uses mixed acid (HCl + H2SO4) to etch halloysite, so that the etching effect of halloysite is better. Traditional single acid etching can remove part of the aluminum in a short time, and the inner diameter of the halloysite nanotube increases. In the present invention, after more aluminum is removed in a short time by mixed acid etching, the inner diameter of the halloysite nanotube is further expanded. Precise dealumination treatment forms uniform nanopores on the surface of halloysite, which is conducive to the rapid migration of ions and blocks the penetration of macromolecules.
[0056] 3. The present invention uses acid and alkali to etch halloysite for the first time. After the acid etching is completed, the sodium aluminum silicate HNT with the required cubic structure is reconstructed by adjusting the temperature and time of the alkali treatment. The original nanotubular halloysite is broken into flakes after alkali heating treatment, and then reconstructed to form a stable cubic structure. The alkali treatment causes the -O-Si-O- continuum to be hydroxylated, forming some active centers with -SiOH groups, which can not only increase hydrophilicity but also promote ion exchange.
[0057] 4. The present invention composites cubic sodium aluminum silicate HNT with refined homogeneous SPEEK. The incorporation of cubic HNT can avoid the deterioration of mechanical properties due to excessive sulfonation, making it highly stable; at the same time, HNT itself has ion screening properties, which can not only provide multiple ion transmission channels, but also effectively screen macromolecules to reduce penetration, thereby extending the cycle life of the battery, while improving the ion selectivity and mechanical properties of the composite membrane, and improving the overall performance of the battery. In addition, since the hydroxyl groups on the surface of SPEEK are active groups, they are more easily hydrolyzed after pretreatment to complete ion exchange, so SPEEK is usually electronegative. The surface of HNT after alkali treatment is also rich in hydroxylation and has electronegativity. Since electrostatic interactions are conducive to the rapid jumping transmission of sodium ions, the ion conductivity of the composite membrane is increased.
[0058] 5. The present invention combines cubic sodium aluminum silicate HNT with traditional perfluorosulfonic acid membrane. The cubic HNT with sieving properties is added to PFSA to improve its poor ion selectivity, thereby extending the cycle life of the battery, improving the ion selectivity and mechanical properties of the composite membrane, and improving the overall performance of the battery. In addition, the sulfonic acid groups on the PFSA side chains can be pretreated (depending on the acid-base system used by the diaphragm, sodium hydroxide, potassium hydroxide, sulfuric acid, etc. can be used for pretreatment) to accelerate the conduction of Na + , K + , H + After acid-base treatment, the surface of HNT is also rich in hydroxylation and electronegative. The electrostatic interaction is conducive to the rapid hopping transmission of ions, which increases the ion conductivity of the composite membrane.
[0059] 6. The composite diaphragm preparation process of the present invention uses low-cost and environmentally friendly raw materials, the equipment used is easy to operate, the preparation process is very simple, and the solution casting method used is conducive to the batch preparation of diaphragms. It has the characteristics of industrial practicality and is helpful to promote the development of commercial composite diaphragm materials for liquid flow batteries and promote the commercial production of liquid flow batteries.
[0060] In summary, the present invention effectively reduces the active ion permeability, improves the ion selectivity, and enhances the chemical stability and mechanical properties of the composite membrane by adding the new sodium aluminum silicate HNT while ensuring the high ion conductivity of the composite membrane. The SPEEK / HNT composite membrane prepared by the solution casting method exhibits high ion conductivity, excellent ion selectivity, good chemical stability and excellent mechanical properties. In liquid flow batteries, the membrane has high capacity retention, high efficiency, low self-discharge rate, low polarization and low preparation cost, and is suitable for a variety of liquid flow battery systems. The SPEEK / HNT composite membrane exhibits excellent capacity retention and cycle stability in liquid flow battery applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0061] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0062] Figure 1a is a TEM image of original halloysite, where the inset in the upper right corner is a TEM image of halloysite with an enlarged inner diameter after mixed acid etching.
[0063] Figure 1b is a SEM image of the sodium aluminum silicate HNT after acid-base pretreatment in Example 1.
[0064] Figure 2 is the SEM image of the SPEEK / HNT composite membrane in Example 1.
[0065] Figure 3 This is a capacity-voltage comparison chart of SPEEK / HNT-2 composite membrane and Nafion used in zinc-iron liquid flow batteries.
[0066] Figure 4 This is a comparison chart of the discharge capacity of SPEEK / HNT-2 composite membrane and Nafion used in zinc-iron liquid flow batteries.
[0067] Figure 5 This is a comparison chart of the coulombic efficiency of SPEEK / HNT-2 composite membrane and Nafion used in zinc-iron liquid flow batteries.
[0068] Figure 6 is a SEM image of the sodium aluminum silicate HNT after acid-base pretreatment in Example 2.
[0069] Figure 7 This is the SEM image of the SPEEK / HNT-1 composite membrane in Example 2.
[0070] Figure 8 This is a comparison chart of the discharge capacity retention rate of SPEEK / HNT-1 composite membrane and Nafion used in zinc-iron liquid flow batteries.
[0071] Fig. 9 is a SEM image of the sodium aluminum silicate HNT after acid-base pretreatment in Example 3.
[0072] Fig.10 This is the SEM image of the SPEEK / HNT-3 composite membrane in Example 3.
[0073] Fig.11 This is a comparison chart of the discharge capacity retention rate of SPEEK / HNT-3 composite membrane and Nafion used in zinc-iron liquid flow batteries.
[0074] Fig.12 This is the SEM image of the PFSA / HNT-2 composite membrane in Example 4.
[0075] Fig.13 This is the capacity decay graph of PFSA / HNT-2 composite membrane and Nafion212 used in zinc-iron liquid flow battery.
[0076] Fig.14 This is the SEM image of the halloysite after single HCl treatment in Comparative Example 2.
[0077] Fig.15 This is the SEM image of the halloysite after single H2SO4 treatment in Comparative Example 3.
[0078] Fig.16 This is the SEM image of the halloysite in Comparative Example 4.
[0079] Fig.17 This is the SEM image of the halloysite in Comparative Example 5.
[0080] Fig.18 This is the SEM image of the halloysite in Comparative Example 6.
[0081] Fig.19 This is the SEM image of the halloysite in Comparative Example 7.
[0082] Fig. 20 This is the SEM image of the halloysite in Comparative Example 8.
[0083] Fig.21 This is the SEM image of the halloysite in Comparative Example 9.
[0084] Fig. 22 This is a graph showing the energy efficiency of the SPEEK membrane of Comparative Example 10 for a zinc-iron flow battery.
[0085] Fig.23 This is a cycle diagram of the SPEEK membrane of Comparative Example 11 used in a zinc-iron flow battery.
[0086] Fig.24 This is a graph showing the coulombic efficiency and energy efficiency of the SPEEK membrane of comparative example 12 when used in a zinc-iron liquid flow battery.
[0087] Fig.25 This is a graph of the discharge capacity of the SPEEK membrane of Comparative Example 13 used in a zinc-iron flow battery.
[0088] Fig.26 These are the test results of the hydrophilic properties of unmodified halloysite and modified halloysite.
[0089] Fig. 27 It is a comparison chart of the ion permeability of the composite membrane obtained in Examples 1, 2, and 3 and Nafion212 and SPEEK membranes. DETAILED DESCRIPTION
[0090] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0091] In the specific implementation process, the present invention uses SPEEK as the matrix, adds modified sodium aluminum silicate HNT, and prepares the SPEEK / HNT composite membrane by solution casting. SPEEK with uniform segments is prepared by refining and homogenizing SPEEK, and then ion exchange is completed by alkali pretreatment. Porous halloysite is prepared by mixed acid (HCl+H2SO4) etching, and the halloysite is reconstructed by alkaline solution. After the two are compounded, a SPEEK / HNT composite membrane with stable chemical properties and fast ion conductivity is obtained, which is applied to liquid flow batteries to show excellent battery performance.
[0092] The present invention is further described below in conjunction with embodiments and drawings.
[0093] S1: Preparation of dealuminated halloysite by mixed acid etching.
[0094] S11: Put the halloysite powder into a mixed acid (HCl+H2SO4) solution, the mass fraction of the HCl solution is 38%, the mass volume ratio of the HNT powder to the HCl solution is 1 / 30~1 / 10 g / mL; the concentration of the H2SO4 solution is 1.0~3.0 M; the mass volume ratio of the HNT powder to the H2SO4 solution is 1 / 20~1 / 5 g / mL;
[0095] S12: stirring the mixed solution at 20°C to 60°C for 3 to 6 hours, expanding the inner cavity of the halloysite through a dealumination process and adjusting the pore size on the surface;
[0096] S13: then washing with deionized water until the pH is close to 7, and drying to obtain halloysite powder. The specific surface area, pore volume and loading capacity of halloysite are increased by removing aluminum through acid leaching treatment.
[0097] S2: Preparation of novel cubic HNTs.
[0098] S21: The halloysite powder obtained by acid etching is placed in a 0.5-2.0 M sodium hydroxide solution. Depending on the system, sodium hydroxide, potassium hydroxide, etc. can be used here.
[0099] S22: Reconstruction of the structure at 40-80 °C, reaction time 48-72 h;
[0100] S23: Then, a large amount of deionized water is used to wash the product until it is neutral, and then centrifugally dried to obtain sodium aluminum silicate HNT with a cubic structure.
[0101] Through alkali treatment, the -O-Si-O- of halloysite is continuously hydroxylated to form some active centers with -SiOH groups, which will greatly improve its hydrophilicity and ion conductivity. The modified halloysite prepared by precise control has its morphology transformed from tubular to a cubic structure with better support and conductivity, and an ion selection layer with a microporous structure is formed on the surface to improve the ion conductivity of the membrane and block the penetration of large-sized ions.
[0102] S3: Preparation of fine and homogeneous sulfonated polyetheretherketone.
[0103] S31: Add concentrated sulfuric acid to n containers respectively, the mass percentage of concentrated sulfuric acid is 98%; add polyetheretherketone (PEEK) to each container, the mass volume ratio of PEEK to concentrated sulfuric acid in each container is 1 / 15-1 / 10 g / mL; the container is a round-bottom flask with a capacity of 25ml~50ml; here n≥2;
[0104] S32: stirring at 20°C to 60°C for 40 to 60 minutes;
[0105] S33: After homogenization is completed, the solutions in the n containers are mixed together, and stirred at 60-80° C. for 20-40 min, with the stirring speed being 500-700 rpm; thus completing the long chain grafting;
[0106] S34: After the reaction is completed, the reactants are repeatedly washed with deionized water until they are neutral, and then dried in an oven to obtain a sulfonated polyetheretherketone with a sulfonation degree of 55% to 65%.
[0107] S4: Ionization treatment of sulfonated polyetheretherketone.
[0108] S41: The obtained sulfonated polyetheretherketone material is placed in a 0.5-2.0 M sodium hydroxide solution and immersed at a constant temperature of 30-50°C for 2-4 hours to complete the replacement of sodium ions; sodium hydroxide, potassium hydroxide, etc. can also be used for different systems to obtain sodium ion type sulfonated polyetheretherketone and potassium ion type sulfonated polyetheretherketone, respectively.
[0109] S42: After the reaction is completed, the reactants are repeatedly washed with deionized water until the pH of the washing solution is neutral, and then dried in an oven to obtain sodium ion type sulfonated polyetheretherketone.
[0110] S5: Preparation of halloysite-modified polymer composite membrane.
[0111] S51: add the sulfonated polyetheretherketone of S4 to a high boiling point organic solvent, wherein the high boiling point organic solvent is any one of dimethyl sulfoxide, dimethylformamide, and dimethylacetamide; the mass volume ratio of the sulfonated polyetheretherketone to the high boiling point organic solvent is 1 / 20-1 / 32 g / mL; pre-stir for 2-6 h at 58-62°C;
[0112] S52: Then add HNT prepared in S2, the mass of which is 1-3% of the mass of sulfonated polyetheretherketone, and continue stirring for 1-4 h;
[0113] S53: After ultrasonic treatment for 14-16 min, the composite membrane was obtained by drying at 78-82°C for 11.5-12.5 h using the solution casting method, and then the temperature was adjusted to 98-102°C for drying for 1.8-2.2 h. The role of ultrasonic treatment is to remove some bubbles that may be generated by stirring and make the mixed solution more uniform.
[0114] If the shredded and dried perfluorosulfonic acid membrane is used in S51, the obtained halloysite-modified polymer composite membrane needs to be heated in an ionizing solvent and then soaked in deionized water for storage; the ionizing solvent is any one of NaOH, KOH, and H2SO4, with a concentration of 0.5~2.0 M; the heating temperature is 50~70℃, and the heating time is 1.0 h~2.0 h.
[0115] Example 1
[0116] S1: Preparation of de-Al halloysite by mixed acid etching.
[0117] S11: The halloysite powder was placed in a mixed acid (HCl+H2SO4) solution, the mass volume ratio of HNT powder to HCl aqueous solution was 1 / 20 g / mL, the concentration of H2SO4 solution was 2 M, and the mass volume ratio of HNT powder to H2SO4 aqueous solution was 1 / 10 g / mL;
[0118] S12: stirring the mixed solution at 40 °C for 4 h, expanding the inner cavity of the halloysite through the process of removing Al, and adjusting the pore size on the surface;
[0119] S13: then washing with deionized water until the pH is close to 7, and drying to obtain halloysite powder.
[0120] S2: Preparation of novel cubic HNTs.
[0121] S21: The halloysite powder obtained by acid etching is placed in a 1M sodium hydroxide solution:
[0122] S22: structural reconstruction at 60 °C, reaction time is 60 h;
[0123] S23: Then, a large amount of deionized water is used to wash the product until it is neutral, and then centrifugally dried to obtain sodium aluminum silicate HNT with a cubic structure.
[0124] S3: Preparation of fine and homogeneous sulfonated polyetheretherketone.
[0125] S31: 16 parts of polyetheretherketone (PEEK) were added to 16 parts of concentrated sulfuric acid, and the mass volume ratio of PEEK to concentrated sulfuric acid was 1 / 13 g / mL;
[0126] S32: Stir at 40 °C for 50 min;
[0127] S33: After homogenization, 16 solutions were mixed together and stirred at 70°C for 30 min at a stirring speed of 600 rpm to complete the long chain grafting;
[0128] S34: After the reaction is completed, the reactants are repeatedly washed with deionized water until they are neutral, and then dried in an oven to obtain a sulfonated polyetheretherketone with a sulfonation degree of 60%.
[0129] S4: Ionization treatment of sulfonated polyetheretherketone.
[0130] S41: placing the obtained sulfonated polyetheretherketone material in a 1M sodium hydroxide solution and immersing it at a constant temperature of 40° C. for 4 hours to complete the replacement of sodium ions;
[0131] S42: After the reaction is completed, the reactants are repeatedly washed with deionized water until they are neutral, and then dried in an oven to obtain sodium ion type sulfonated polyetheretherketone.
[0132] S5: Preparation of SPEEK / HNT composite membrane.
[0133] S51: Add the dried sodium ion type sulfonated polyetheretherketone to the high boiling point organic solvent dimethyl sulfoxide, the mass volume ratio of the sodium ion type sulfonated polyetheretherketone to the high boiling point organic solvent is 1 / 28 g / mL; pre-stir for 4 h at 60°C;
[0134] S52: Then, 2% of the mass of sulfonated polyetheretherketone (SPEEEK) HNT was added and stirring was continued for 2 h;
[0135] S53: After ultrasonic treatment for 15 min, the mixture was dried at 80°C for 12 h using a solution casting method, and then the temperature was adjusted to 100°C and dried for 2 h to obtain a SPEEK / HNT-2 composite membrane.
[0136] The relevant performance data of Example 1 are as follows:
[0137] Figure 1a is the SEM image of the original halloysite. Figure 1b The SEM image of sodium aluminum silicate HNT after acid-base pretreatment. The inset in the upper right corner is a TEM image of halloysite with an enlarged inner diameter after mixed acid etching.
[0138] like Figure 1b As shown, the prepared sodium aluminum silicate HNT has a stable cubic structure.
[0139] like Figure 2 As shown, the modified halloysite is evenly distributed in the SPEEK matrix, and the diaphragm has a smooth surface, a dense structure, and no obvious holes and impurities, which ensures the uniformity and mechanical stability of the diaphragm.
[0140] Figure 3 It can be seen that the zinc-iron flow battery equipped with SPEEK / HNT-2 composite membrane has a smaller polarization than the zinc-iron flow battery equipped with Nafion212.
[0141] like Figure 4 As shown in the figure, the capacity of the zinc-iron flow battery equipped with Nafion212 decays rapidly. This is because the ion selectivity of the diaphragm is poor, and self-discharge caused by ion cross-contamination occurs, resulting in rapid capacity decay. In contrast, the SPEEK / HNT-2 composite membrane has a better capacity retention rate.
[0142] Figure 5It can be seen that the coulombic efficiency of the zinc-iron flow battery assembled with the SPEEK / HNT-2 composite membrane is always stable at nearly 100%, indicating that the addition of modified halloysite not only promotes ion transport, but also improves the ion selectivity and chemical stability of the membrane. In addition, the cost of the composite membrane is much lower than that of Nafion212, so this example proves that the SPEEK / HNT-2 composite membrane has good application prospects in zinc-iron flow batteries.
[0143] Example 2
[0144] S1: Preparation of de-Al halloysite by mixed acid etching.
[0145] S11: Put the halloysite powder into a mixed acid (HCl+H2SO4) solution, the mass fraction of the HCl solution is 38%, the mass volume ratio of the HNT powder to the HCl solution is 1 / 30 g / mL; the concentration of the H2SO4 solution is 1.0 M; the mass volume ratio of the HNT powder to the H2SO4 solution is 1 / 20 g / mL;
[0146] S12: stirring the mixed solution at 60°C for 3h, expanding the inner cavity of the halloysite through the process of removing Al, and adjusting the pore size on the surface;
[0147] S13: then washing with deionized water until the pH is close to 7, and drying to obtain halloysite powder.
[0148] S2: Preparation of novel cubic HNTs.
[0149] S21: The halloysite powder obtained by acid etching is placed in a 0.5 M potassium hydroxide solution; since the reaction mechanism is the same, potassium chloride solution can be used here;
[0150] S22: structural reconstruction at 40 °C, reaction time is 72 h;
[0151] S23: The product is then washed with a large amount of deionized water until it is neutral, and then centrifuged and dried to obtain potassium aluminum silicate HNT with a cubic structure.
[0152] S3: Preparation of fine and homogeneous sulfonated polyetheretherketone.
[0153] S31: 16 parts of polyetheretherketone (PEEK) are added to 16 parts of concentrated sulfuric acid, the mass percentage of the concentrated sulfuric acid is 98%; the mass volume ratio of PEEK to concentrated sulfuric acid is 1 / 15 g / mL;
[0154] S32: stirring at 60°C for 40 min;
[0155] S33: After homogenization, 16 solutions were mixed together and stirred at 60°C for 40 min at a stirring speed of 500 rpm to complete the long chain grafting;
[0156] S34: After the reaction is completed, the reactants are repeatedly washed with deionized water until they are neutral, and then dried in an oven to obtain sulfonated polyetheretherketone with a sulfonation degree of 65%.
[0157] S4: Ionization treatment of sulfonated polyetheretherketone.
[0158] S41: placing the obtained sulfonated polyetheretherketone material in a 0.5M potassium hydroxide solution and soaking it at a constant temperature of 30°C for 4 h to complete the replacement of potassium ions; since the reaction mechanism is the same, a potassium chloride solution can be used here;
[0159] S42: After the reaction is completed, the reactants are repeatedly washed with deionized water until the pH of the washing solution is neutral, and then dried in an oven to obtain sodium ion type sulfonated polyetheretherketone.
[0160] S5: Preparation of SPEEK / HNT composite membrane.
[0161] S51: adding potassium ion type sulfonated polyetheretherketone to high boiling point organic solvent dimethylformamide; the mass volume ratio of potassium ion type sulfonated polyetheretherketone to high boiling point organic solvent is 1 / 32 g / mL; pre-stirring treatment is performed at 62°C for 2 hours;
[0162] S52: then add 1% of the HNT by weight of sulfonated polyetheretherketone, and continue stirring for 1 hour;
[0163] S53: After ultrasonication for 14 min, the mixture was dried at 78 °C for 12.5 h using a solution casting method, and then the temperature was adjusted to 98 °C and dried for 2.2 h to obtain a SPEEK / HNT-1 composite membrane.
[0164] The relevant performance data of Example 2 are as follows:
[0165] Figure 6 is the SEM image of sodium aluminum silicate HNT after acid-base pretreatment. Figure 6 As shown, the prepared sodium aluminum silicate HNT has a relatively regular cubic structure.
[0166] like Figure 7 As shown, the modified halloysite is evenly distributed in the SPEEK matrix, and the surface of the diaphragm is relatively smooth, with a dense structure and no obvious holes and impurities, which ensures the uniformity and mechanical stability of the diaphragm.
[0167] like Figure 8As shown in the figure, the capacity of the zinc-iron flow battery equipped with Nafion212 decays rapidly. This is because the ion selectivity of the diaphragm is poor, and self-discharge caused by ion cross-contamination occurs, resulting in rapid capacity decay. In contrast, the SPEEK / HNT-1 composite membrane has a better capacity retention rate.
[0168] Example 3
[0169] S1: Preparation of de-Al halloysite by mixed acid etching.
[0170] S11: Put the halloysite powder into a mixed acid (HCl+H2SO4) solution, the mass fraction of the HCl solution is 38%, the mass volume ratio of the HNT powder to the HCl solution is 1 / 10 g / mL; the concentration of the H2SO4 solution is 3.0 M; the mass volume ratio of the HNT powder to the H2SO4 solution is 1 / 5 g / mL;
[0171] S12: stirring at 20 °C for 6 h, expanding the inner cavity of the halloysite through the process of removing Al, and adjusting the pore size on the surface;
[0172] S13: then washing with deionized water until the pH is close to 7, and drying to obtain halloysite powder.
[0173] S2: Preparation of novel cubic HNTs.
[0174] S21: putting the halloysite powder obtained by acid etching into a 2.0 M sodium chloride solution;
[0175] S22: structural reconstruction at 80 °C, reaction time is 48 h;
[0176] S23: Then, a large amount of deionized water is used to wash the product until it is neutral, and then centrifugally dried to obtain sodium aluminum silicate HNT with a cubic structure.
[0177] S3: Preparation of fine and homogeneous sulfonated polyetheretherketone.
[0178] S31: 16 parts of polyetheretherketone (PEEK) were added to 16 parts of concentrated sulfuric acid, the mass percentage of concentrated sulfuric acid was 98%; the mass volume ratio of PEEK to concentrated sulfuric acid was 1 / 10 g / mL;
[0179] S32: stirring at 20°C for 60 min;
[0180] S33: After homogenization, 16 solutions were mixed together and stirred at 80° C. for 20 min at a stirring speed of 700 rpm to complete long chain grafting;
[0181] S34: After the reaction is completed, the reactants are repeatedly washed with deionized water until they are neutral, and then dried in an oven to obtain sulfonated polyetheretherketone with a sulfonation degree of 55%.
[0182] S4: Ionization treatment of sulfonated polyetheretherketone.
[0183] S41: placing the obtained sulfonated polyetheretherketone material in a 2.0 M sodium chloride solution and immersing it at a constant temperature of 50° C. for 2 h to complete the replacement of sodium ions;
[0184] S42: After the reaction is completed, the reactants are repeatedly washed with deionized water until the pH of the washing solution is neutral, and then dried in an oven to obtain sodium ion type sulfonated polyetheretherketone.
[0185] S5: Preparation of SPEEK / HNT composite membrane.
[0186] S51: adding sodium ion type sulfonated polyetheretherketone to high boiling point organic solvent dimethylacetamide; the mass volume ratio of sodium ion type sulfonated polyetheretherketone to high boiling point organic solvent is 1 / 20 g / mL; pre-stirring treatment is performed at 58°C for 6 h;
[0187] S52: Then, 3% of the mass of sulfonated polyetheretherketone (SPEEEK) HNT was added and stirring was continued for 4 h;
[0188] S53: After ultrasonication for 16 min, the mixture was dried at 82 °C for 11.5 h using a solution casting method, and then the temperature was adjusted to 102 °C and dried for 1.8 h to obtain a SPEEK / HNT-3 composite membrane.
[0189] The relevant performance data of Example 3 are as follows:
[0190] like Fig. 9 As shown, the prepared sodium aluminum silicate HNT has a relatively regular cubic structure.
[0191] like Fig.10 As shown, the modified halloysite is evenly distributed in the SPEEK matrix, and the surface of the diaphragm is relatively smooth, with a dense structure and no obvious holes and impurities, which ensures the uniformity and mechanical stability of the diaphragm.
[0192] like Fig.11 As shown in the figure, the capacity of the zinc-iron flow battery equipped with Nafion212 decays rapidly. This is because the ion selectivity of the diaphragm is poor, and self-discharge caused by ion cross-contamination occurs, resulting in rapid capacity decay. In contrast, the SPEEK / HNT-3 composite membrane has a better capacity retention rate.
[0193] Example 4
[0194] The domestic perfluorosulfonic acid membrane PFSA membrane was cut into pieces and dried at 100°C, and the dried PFSA was added to the high boiling point organic solvent dimethylformamide, with the mass ratio of PFSA to the high boiling point organic solvent being 1 / 28; it was pre-stirred for 4 h under heating conditions at 60°C; then 2% of the mass of S4 HNT of sulfonated polyetheretherketone was added, and stirring was continued for 2 h; after ultrasonic treatment for 15 min, the solution casting method was used to bake at 80°C for 12 h, and the temperature was adjusted to 100°C and dried for 2 h to obtain the PFSA / HNT-2 composite membrane.
[0195] PFSA / HNT-2 was heated in 1.0 M ionizing solvent NaOH at 60°C for 90 min, and then soaked in deionized water for later use. For different systems, the ionizing solvent can be KOH or H2SO4.
[0196] The relevant performance data of Example 4 are as follows:
[0197] like Fig.12 As shown, the modified halloysite is evenly distributed in the PFSA matrix, and the surface of the diaphragm is relatively smooth, with a dense structure and no obvious holes and impurities, which ensures the uniformity and mechanical stability of the diaphragm.
[0198] like Fig.13 As shown in the figure, the capacity of the zinc-iron flow battery equipped with Nafion212 decays rapidly. This is because the ion selectivity of the diaphragm is poor, and self-discharge caused by ion cross-contamination occurs, resulting in rapid capacity decay. In contrast, the PFSA / HNT-2 composite membrane has a better capacity retention rate.
[0199] Example 5
[0200] The difference from Example 4 is:
[0201] PFSA / HNT-2 was heated in 0.5 M ionized solvent KOH at 50 °C for 60 min and then soaked in deionized water for use.
[0202] Example 6
[0203] The difference from Example 4 is:
[0204] PFSA / HNT-2 was heated in 2.0 M ionized solvent H2SO4 at 70°C for 120 min and then soaked in deionized water for use.
[0205] Comparative Example 1
[0206] The difference from Example 1 is that:
[0207] S3: PEEK powder was completely dried at 80°C, and concentrated sulfuric acid was heated to 60°C. The mass volume ratio of PEEK to concentrated sulfuric acid was 1 / 12 (g / mL). After uniform mixing, it was vigorously stirred at 700 r / min for 2 h. After the reaction, it was ultrasonicated for 15 min, and then poured into ice water while stirring. After the reaction, the reaction product was continuously washed with deionized water until it was neutral, dried at room temperature, and dried in an oven at 80°C for 24 h to obtain dry SPEEK. The sulfonation degree of SPEEK was measured by ion exchange method to be about 60%.
[0208] The relevant performance data of this embodiment are as follows:
[0209] The SPEEK obtained by the traditional method is a non-homogeneous SPEEK. Compared with the homogeneous SPEEK of Example 1, the appearance is uneven, and due to the uneven sulfonation, the sulfonation degrees measured multiple times also have a certain difference.
[0210] Comparative Example 2
[0211] The difference from Example 1 is that:
[0212] S1: Halloysite powder was placed in a single HCl solution with a mass volume ratio of HNT powder and HCl aqueous solution of 1 / 20 g / mL. The solution was stirred at 40 °C for 4 h. The inner cavity of the halloysite was enlarged by the process of de-Al removal and the pore size of the surface was adjusted. The solution was then washed with deionized water until the pH was close to 7 and dried to obtain the halloysite powder.
[0213] like Fig.14 As shown, the single HCl etching efficiency is too low, resulting in the inability to generate sodium aluminosilicate HNTs with stable cubic structure after subsequent alkali treatment.
[0214] Comparative Example 3:
[0215] The difference from Example 1 is that:
[0216] S1: Halloysite powder was placed in a single H2SO4 solution with a mass volume ratio of HNT powder and H2SO4 aqueous solution of 1 / 20 g / mL. The solution was stirred at 40°C for 4 h. The inner cavity of the halloysite was enlarged by the process of de-Al removal and the pore size of the surface was adjusted. The solution was then washed with deionized water until the pH value was close to 7 and dried to obtain the halloysite powder.
[0217] like Fig.15 As shown, the single H2SO4 etching efficiency is too low, resulting in the inability to generate sodium aluminum silicate HNTs with a stable cubic structure after subsequent alkali treatment.
[0218] Comparative Example 4
[0219] The difference from Example 1 is that:
[0220] In S22, the reaction temperature is 30°C;
[0221] like Fig.16 As shown, the alkali etching temperature is not high enough, which makes it impossible to destroy and reorganize the original structure of halloysite, so the halloysite still maintains a tubular structure.
[0222] Comparative Example 5
[0223] The difference from Example 1 is that:
[0224] In S22, the reaction temperature is 90°C;
[0225] like Fig.17 As shown, the alkaline etching temperature is too high, causing the halloysite structure to be destroyed into a flaky structure and unable to reassemble.
[0226] Comparative Example 6
[0227] The difference from Example 1 is that:
[0228] In S22, the reaction time is 45 h;
[0229] like Fig.18 As shown, the alkali etching time is not enough, resulting in the destruction of the original structure of halloysite and the reorganization of the cube with an irregular morphology.
[0230] Comparative Example 7
[0231] The difference from Example 1 is that:
[0232] In S22, the reaction time is 75 h;
[0233] like Fig.19 As shown, the alkali etching time is too long, causing the halloysite to reorganize into cubes, and then some cubes are broken into flakes again.
[0234] Comparative Example 8
[0235] The difference from Example 1 is that:
[0236] In S11, the mass volume ratio of HNT powder and HCl solution was 1 / 40 g / mL;
[0237] like Fig. 20 As shown, due to the excessive amount of HCl, the halloysite structure formed by the later alkali etching is unstable, and a small part of it exists in the form of flakes.
[0238] Comparative Example 9
[0239] The difference from Example 1 is that:
[0240] In S11, the mass volume ratio of HNT powder and HCl solution was 1 / 5 g / mL;
[0241] like Fig.21 As shown, due to the small amount of HCl, the acid etching in the early stage was insufficient, so most of the halloysite still existed in the form of tubes.
[0242] Comparative Example 10
[0243] The difference from Example 1 is that:
[0244] In S11, the mass volume ratio of HNT powder and H2SO4 solution was 1 / 30 g / mL;
[0245] like Fig. 22 As shown, due to the excessive amount of H2SO4, the halloysite structure formed by the later alkali etching is unstable, and a small part of it exists in the form of flakes.
[0246] Comparative Example 11
[0247] The difference from Example 1 is that:
[0248] In S11, the mass volume ratio of HNT powder and H2SO4 solution was 1 / 2 g / mL;
[0249] like Fig.23 As shown, due to the small amount of H2SO4 and insufficient acid etching in the early stage, most of the halloysite still exists in tubular form.
[0250] Comparative Example 12
[0251] The difference from Example 1 is that:
[0252] In S32, during the sulfonation reaction, the stirring time was 30 min;
[0253] Since the sulfonation stirring time is insufficient, the sulfonation degree of the prepared SPEEK is low and uneven.
[0254] Comparative Example 13
[0255] The difference from Example 1 is that:
[0256] In S32, during the sulfonation reaction, the stirring time was 70 min;
[0257] Since the sulfonation stirring time is too long, the prepared SPEEK has a high degree of sulfonation, and since the sulfonation degree is too high, the SPEEK will be quickly dehydrated during the drying process, forming a thin and brittle SPEEK.
[0258] Comparative Example 14
[0259] The difference from Example 1 is that:
[0260] In S33, the solutions are mixed together and stirred at 50° C.;
[0261] Since the sulfonation temperature is too low, the sulfonation degree of the SPEEK is low, so the ion conductivity of the membrane is low. Fig.24 As shown, the separator is used in a zinc-iron flow battery, and the energy efficiency of the battery is extremely low.
[0262] Comparative Example 15
[0263] The difference from Example 1 is that:
[0264] In S33, the solutions are mixed together and stirred at 90° C.;
[0265] Since the sulfonation temperature is too high, the sulfonation degree of the SPEEK is too high, so the mechanical stability of the diaphragm is poor. Fig.25 As shown, when the separator is used in zinc-iron flow batteries, the cycle life of the battery is extremely short.
[0266] like Fig.26 , it can be seen that the contact angle of the modified halloysite is smaller, so the hydrophilicity is better.
[0267] like Fig. 27 It can be seen that the composite membranes prepared in Examples 1-3 significantly reduced the Fe(CN)6 3- This helps prevent side reactions and prolong battery life.
[0268] Table 1 is a comparison table of the thickness, water absorption, swelling rate and conductivity of the composite membrane, Nafion212 and SPEEK membrane prepared in Examples 1-3, as shown in Table 1. It can be seen that the composite membrane prepared in Examples 1-3 significantly improves the conductivity.
[0269] Table 1 Comparison of thickness, water absorption, swelling rate and conductivity of composite membrane, Nafion212 and SPEEK membrane prepared in Examples 1-3
[0270]
[0271] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referred to each other, and each embodiment focuses on the differences from other embodiments. In particular, for the system embodiment, since it is basically similar to the method embodiment, the description is relatively simple, and the relevant parts can be referred to the partial description of the method embodiment.
[0272] The above description is only a preferred embodiment of the present invention and is not intended to limit the protection scope of the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention are included in the protection scope of the present invention.
Claims
1. A method for preparing a HNT-modified polymer composite membrane, characterized in that: The following steps are involved: S1: Preparation of dealuminated HNTs; The halloysite powder is placed in a mixed acid solution, wherein the mixed acid is a mixed solution composed of HCl solution and H2SO4 solution, the mass fraction of the HCl solution is 38%, the mass volume ratio of the HNT powder to the HCl solution is 1 / 30~1 / 10 g / mL; the concentration of the H2SO4 solution is 1.0~3.0 M; the mass volume ratio of the HNT powder to the H2SO4 solution is 1 / 20~1 / 5 g / mL; S2: Preparation of modified HNTs using dealuminated HNTs; S3: Preparation of sulfonated polyetheretherketone; S31: Add concentrated sulfuric acid to n containers respectively, the mass percentage of concentrated sulfuric acid is 98%; add polyetheretherketone to each container, the mass volume ratio of PEEK to concentrated sulfuric acid in each container is 1 / 15-1 / 10 g / mL; the container is a round-bottom flask with a capacity of 25ml~50ml; n≥2; S32: stirring at 20°C to 60°C for 40 to 60 minutes; S33: After homogenization is completed, the solutions in the n containers are mixed together, and stirred at 60-80° C. for 20-40 min, with the stirring speed being 500-700 rpm; thus completing the long chain grafting; S34: After the reaction is completed, the reactant is repeatedly washed with deionized water until it is neutral, and then dried in an oven to obtain a sulfonated polyetheretherketone with a sulfonation degree of 55% to 65%; S4: ionization treatment of sulfonated polyetheretherketone; S5: Prepare HNT-modified polymer composite membrane using the modified HNT and sulfonated polyetheretherketone or perfluorosulfonic acid membrane obtained in S4.
2. The method for preparing a HNT-modified polymer composite membrane according to claim 1, characterized in that: The S1 includes: S11: placing HNT into a mixed acid solution and controlling the mass volume ratio of HNT to acid; S12: stirring the mixed solution to perform dealumination operation on the HNT; S13: The product obtained in S12 is washed with deionized water until it becomes neutral, and dried to obtain dealuminated HNT.
3. The method for preparing a HNT-modified polymer composite membrane according to claim 2, characterized in that: In the S12, the mixed solution is stirred at 20° C. to 60° C. for 3 to 6 hours.
4. The method for preparing a HNT-modified polymer composite membrane according to claim 1, characterized in that: The S2 includes: S21: placing the dealuminated HNT obtained in S1 into an alkaline solution; S22: reacting at a constant temperature; S23: The product is cleaned with deionized water and dried to obtain modified HNTs.
5. The method for preparing a HNT-modified polymer composite membrane according to claim 4, characterized in that: In S21, The alkaline solution is any one of sodium hydroxide, potassium hydroxide, sodium chloride and potassium chloride; the concentration of the alkaline solution is 0.5~2.0 M; In S22, the temperature is 40-80 °C and the reaction time is 48-72 h; The structure of the modified HNT obtained in S23 is a cube.
6. The method for preparing a HNT-modified polymer composite membrane according to claim 1, characterized in that: The S4 includes: S41: placing the sulfonated polyetheretherketone obtained in S3 in an alkaline solution and soaking it at a constant temperature; S42: washing the product obtained in S41 with deionized water until it becomes neutral, and drying it to obtain ionized sulfonated polyetheretherketone; In the S41, The alkaline solution is any one of sodium hydroxide, potassium hydroxide, sodium chloride and potassium chloride; the concentration of the alkaline solution is 0.5~2.0 M; The temperature is 40~60℃; the soaking time is 2~4 hours.
7. The method for preparing a HNT-modified polymer composite membrane according to claim 1, characterized in that: The S5 includes: S51: adding the ionized sulfonated polyetheretherketone or the cut and dried perfluorosulfonic acid membrane obtained in S4 into the solvent and stirring; S52: adding the modified HNT obtained in S2 and stirring; S53: performing ultrasonic treatment, followed by drying, to obtain an HNT-modified polymer composite membrane; If the shredded and dried perfluorosulfonic acid membrane is used in S51, the obtained HNT-modified polymer composite membrane needs to be heated in an ionizing solvent with a concentration of 0.5~2.0 M for 1.0 h~2.0 h, and then immersed in deionized water for storage; the ionizing solvent is any one of NaOH, KOH, and H2SO4; the heating temperature is 50~70℃.
8. The method for preparing a HNT-modified polymer composite membrane according to claim 7, characterized in that: In the S51, The solvent is any one of dimethyl sulfoxide, dimethylformamide, and dimethylacetamide; the mass volume ratio of sulfonated polyetheretherketone to organic solvent is 1 / 20-1 / 32 g / mL; stirring is performed at a temperature of 58-62°C for 2-6 hours; In S52, the mass of modified HNT is 1-3% of the mass of sulfonated polyetheretherketone or perfluorosulfonic acid membrane; In S53, the ultrasonic treatment time is 14-16 min; the solution casting method is used for drying; the drying process is drying at 78-82°C for 11.5-12.5 h, and then heating to 98-102°C for drying for 1.8-2.2 h.
Citation Information
Patent Citations
Novel fuel cell with high methanol-resistant performance and preparation method thereof
CN106169587A
Sulfonated polyether-ether-ketone / polyaniline modified halloysite nanotube mixed matrix membrane as well as preparation method and application thereof
CN107789995A